Atomic oxygen dynamics in an air dielectric barrier discharge: a combined diagnostic and modeling approach. (5th June 2015) - Baldus, Sabrina; Schröder, Daniel; Bibinov, Nikita; Schulz-von der Gathen, Volker; Awakowicz, Peter
Abstract Cold atmospheric pressure plasmas are a promising alternative therapy for treatment of chronic wounds, as they have already shown in clinical trials. In this study an air dielectric barrier discharge (DBD) developed for therapeutic use in dermatology is characterized with respect to the plasma produced reactive oxygen species, namely atomic oxygen and ozone, which are known to be of great importance to wound healing. To understand the plasma chemistry of the applied DBD, xenon-calibrated two-photon laser-induced fluorescence spectroscopy and optical absorption spectroscopy are applied. The measured spatial distributions are shown and compared to each other. A model of the afterglow chemistry based on optical emission spectroscopy is developed to cross-check the measurement results and obtain insight into the dynamics of the considered reactive oxygen species. The atomic oxygen density is found to be located mostly between the electrodes with a maximum density of <?CDATA n_O=6× 10^16 ?> <?MML nO=6×1016 ?><inline-graphic xlink:href="ark:/27927/pgj14jg8gnz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> cm <?CDATA ^-3 ?> <?MML −3 ?><inline-graphic xlink:href="ark:/27927/pgj14jg8swg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. Time resolved measurements reveal a constant atomic oxygen density between two high voltage pulses. The ozone is measured up to 3 mm outside the active plasma volume, reaching a maximum value of <?CDATA n_O_3=3× 10^16 ?> <?MML nO3=3×1016 ?><inline-graphic xlink:href="ark:/27927/pgj14jg8f0z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> cm <?CDATA ^-3 ?> <?MML −3 ?><inline-graphic xlink:href="ark:/27927/pgj14jg6qr8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> between the electrodes.